Analisis Penatausahaan Aset Tetap Dalam Meningkatkan Akuntabilitas Laporan Keuangan Daerah - Cikuita Vidi Sastia Daeli; Nadia Marintan Sirait; Keren Eoudia Sitompul; Hamonangan Siallagan (Journal of Innovative and Creativity, 2026)
Fixed asset management is important in realising the accountability of local government financial reports because fixed assets are of material value and are presented in local government balance sheets. Improper management can lead to discrepancies between administrative data and the physical condition of assets, weaken document traceability, and reduce the reliability of fixed asset information in financial reports. This study aims to analyse fixed asset management in improving the accountability of local government financial reports, focusing on bookkeeping, inventory, and reporting. The study uses a qualitative method with a descriptive approach. Data was obtained through in-depth interviews, observations, and documentation studies, then analysed through data reduction, data presentation, and conclusion drawing, and tested for validity through triangulation. The results show that fixed asset management has been carried out in accordance with regulations, but is not yet optimal. The main problems include delays in recording, incomplete supporting documents, incomplete and unsustainable inventory, and discrepancies between administrative data and the physical condition of assets in the field. Fixed asset reporting is in accordance with the format, but the quality of information is highly dependent on the orderliness of bookkeeping and inventory. Improvements are needed through strengthening the competence of officials, optimising the asset information system, improving coordination, and continuous internal supervision.